PENDEKATAN ADAPTIF GURU DI MASA NEW NORMAL UNTUK MENINGKATKAN INTERAKSI PEMBELAJARAN DARING - Erliany Syaodih (Jurnal Soshum Insentif, 2022)
Abstract - New normal or New Habit Adaptation (AKB) is a term commonly used during the COVID-19 pandemic. In the new normal, people return to activities even though they are done gradually and follow provisions, such as health protocols. The activities are referred to in this study are online learning activities carried out by teachers during the COVID-19 pandemic. This online learning is applied by considering the COVID-19 trend in Indonesia is still rising. Online learning is expected to reduce the number of COVID-19 sufferers but online learning methods during its implementation there are several obstacles, especially the lack of student interaction. This phenomenon is certainly an indication that online learning has been less effective. For that, teachers need a special approach which is able to encourage students to learn interactively. The research focuses on teachers' adaptive approach to the new normal in improving student interaction during online learning. To answer the focus and purpose of the study, researchers use a qualitative approach with decryptive studies involving teachers, students, and parents as purposive informants. Based on the research finding and studies obtained conclusions about the level of adaptation that must be done by teachers to improve online learning interaction, namely adaptation in mindset mindset, adaptation in designing learning; adaptation when implementing learning by paying attention to the conditioning and managerial patterns of learning and adaptation in managing various potential and conditions of the learning environment. Abstrak - New normal atau Adaptasi Kebiasaan Baru (AKB) merupakan istilah yang lazim digunakan selama pandemi COVID-19. Di masa new normal masyarakat kembali melakukan aktivitas meskipun dilakukan secara bertahap dan mengikuti ketentuan seperti protokol kesehatan. Aktivitas yang dimaksud pada penelitian ini adalah aktivitas pembelajaran daring yang dilakukan oleh guru selama pandemi COVID-19. Pembelajaran daring ini diterapkan mengingat trend COVID-19 di Indonesia masih naik. Pembelajaran daring ini diharapkan mampu menekan angka penderita COVID-19 namun metode pembelajaran daring saat pelaksanaannya terdapat beberapa hambatan khususnya minimnya interaksi siswa. Fenomena ini tentu saja menjadi indikasi bahwa pembelajaran daring selama ini kurang efektif. Untuk itu, guru memerlukan pendekatan khusus yang mampu mendorong siswa belajar interaktif. Penelitian ini fokus pada pendekatan adaptif guru di masa new normal dalam meningkatkan interaksi siswa selama pembelajaran daring. Untuk menjawab fokus sekaligus tujuan penelitian, peneliti menggunakan pendekatan kualitatif dengan studi dekriptif yang melibatkan guru, siswa, dan orangtua sebagai informan secara purposif. Berdasarkan hasil penelitian dan kajian diperoleh simpulan tentang tingkatan adaptasi yang harus dilakukan guru guna meningkatkan interaksi pembelajaran daring, yaitu adaptasi dalam mindset/ pola berfikir, adaptasi dalam merancang pembelajaran ; adaptasi saat mengimplementasikan pembelajaran dengan memperhatikan pola pengkondisian dan manajerial pembelajaran serta adaptasi dalam mengelola berbagai potensi dan kondisi lingkungan belajar.